Stromal fibroblasts impaired in TGF-beta signaling prime the microenvironment with extracellular hydrogen peroxide and mitogenic factors to support the oncogenic transformation of adjacent epithelia - Tan, Ming Jie (2015)
Epithelial cancers arise when the homeostatic interaction between epithelial cells and stromal